How I Teach It: Endoscopic Evaluation of Hiatal Hernia. Issue 1 (March 2022) - Katz, Philip O.; Ghosh, Gaurav
Hiatal herniation, migration of the gastric cardia from the abdomen cephalad into the chest are commonly present in patients with esophageal symptoms in particular gastroesophageal reflux disease. Three of the four hernia types (sliding type 1 and type 2 or 3 paraesophageal) can be diagnosed by upper endoscopy. Though hernias can also be diagnosed by barium esophagram, computed tomography, and high-resolution manometry, upper endoscopy offers the best opportunity for the foregut physician to carefully assess the patient for hernia size and type, the presence of Cameron lesions in patients with occult anemia and to evaluate the hiatus (flap valve) fully by assessment of the Hill grade in retroflexion. Accurate description of the hiatus in the endoscopy report is invaluable in communication between gastroenterologist and surgeon managing patients with esophageal disease. This "How I teach it" (and video) offers an approach to assessment of the esophageal hiatus during the endoscopic examination.